A measurable physical theory of hyper-correlations beyond quantum mechanics - Farrow, T; Vedral, V; Son, W (IOP Publishing, 2020)
whose non-local character exceeds the bounds allowed by quantum mechanics. Motivated by our observation that an extension of the Schroedinger equation with non-linear terms is directly linked to a relaxation of Born's rule, an axiom of quantum mechanics, we derive a physical theory that accounts for such hyper-correlated states and modifies Born's rule. We model correlated particles with a generalized probability theory whose dynamics are described with a non-linear version of Schr\"odinger's equation and demonstrate how that deviates from the standard formulation of quantum mechanics in experimental probability-prediction. We show also that the violation of the Clauser-Horn-Shimony-Holt inequality, the amount of non-locality, is proportional to the degree of non-linearity, which can be experimentally tested.